2022
DOI: 10.3390/cancers14133113
|View full text |Cite
|
Sign up to set email alerts
|

Solute Carrier Nucleoside Transporters in Hematopoiesis and Hematological Drug Toxicities: A Perspective

Abstract: Anticancer nucleoside analogs produce adverse, and at times, dose-limiting hematological toxicities that can compromise treatment efficacy, yet the mechanisms of such toxicities are poorly understood. Recently, cellular nucleoside transport has been implicated in normal blood cell formation with studies from nucleoside transporter-deficient mice providing additional insights into the regulation of mammalian hematopoiesis. Furthermore, several idiopathic human genetic disorders have revealed nucleoside transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 214 publications
0
1
0
Order By: Relevance
“…[16] However, Grade III or IV adverse events in the surgery following capecitabine group were observed mainly in the metastatic breast cancer, including lymphopenia, neutropenia, and thrombocytopenia. [17] A prospective clinical study of gastroenteropancreatic neuroendocrine tumor patients treated with 177Lu-octreotate peptide receptor radionuclide therapy in combination with capecitabine and temozolomide demonstrated that acute toxicity most often affects platelets during the first cycle of treatment. [18] In this case, acute MDS occurred during the early XELOX courses, which was partially relieved by corresponding drug treatment.…”
Section: Project Amountmentioning
confidence: 99%
“…[16] However, Grade III or IV adverse events in the surgery following capecitabine group were observed mainly in the metastatic breast cancer, including lymphopenia, neutropenia, and thrombocytopenia. [17] A prospective clinical study of gastroenteropancreatic neuroendocrine tumor patients treated with 177Lu-octreotate peptide receptor radionuclide therapy in combination with capecitabine and temozolomide demonstrated that acute toxicity most often affects platelets during the first cycle of treatment. [18] In this case, acute MDS occurred during the early XELOX courses, which was partially relieved by corresponding drug treatment.…”
Section: Project Amountmentioning
confidence: 99%
“…Despite the existence of efficient treatment protocols for childhood ALL, 75% of patients experience therapy-related adverse effects, and 5% die from treatment toxicity (3)(4)(5). Among the most frequent side effects are hematologic adverse events leading to immunosuppression and myelosuppression and, consequently, an increased risk of infections (6,7). Moreover, the effects of chemotherapy toxicity lead to treatment modifications or discontinuations which compromise the outcome (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%